2022
DOI: 10.4014/jmb.2202.02029
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Rare and Abundant Sub-Communities and Physicochemical Properties after Application of Different Chinese Herb Residue Soil Amendments

Abstract: Microbial diversity in the soil is responsive to changes in soil composition. However, the impact of soil amendments on the diversity and structure of rare and abundant sub-communities in agricultural systems is poorly understood. We investigated the effects of different Chinese herb residue (CHR) soil amendments and cropping systems on bacterial rare and abundant sub-communities. Our results showed that the bacterial diversity and structure of these sub-communities in soil had a specific distribution under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[30,32,36] TCMR compost is rich in microorganisms and nutrients that can increase the activity of soil microorganisms. [37][38][39][40][41][42][43] As a fungicide, TCMR can also promote plant growth. [42][43] Although composting has many benefits, it also has some drawbacks for the environment, like odor and greenhouse gas emissions.…”
Section: Aerobic Compostingmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,32,36] TCMR compost is rich in microorganisms and nutrients that can increase the activity of soil microorganisms. [37][38][39][40][41][42][43] As a fungicide, TCMR can also promote plant growth. [42][43] Although composting has many benefits, it also has some drawbacks for the environment, like odor and greenhouse gas emissions.…”
Section: Aerobic Compostingmentioning
confidence: 99%
“…As additions, TCMR, biochar, and vermiculite are often used [30,32,36] . TCMR compost is rich in microorganisms and nutrients that can increase the activity of soil microorganisms [37–43] . As a fungicide, TCMR can also promote plant growth [42–43] …”
Section: Composting Of Tcmrmentioning
confidence: 99%
“…Thus, delineating the differences between abundant and rare taxa is crucial for understanding the processes and functions of microbial communities in ecosystems (Jiao & Lu, 2020a). Previous studies have demonstrated differences in the biogeography, composition, and potential functions of abundant and rare microbial communities in various ecosystems, such as forests (He et al, 2023), farmlands (Chang et al, 2022), lakes , and deserts (Wang et al, 2021). In agricultural soils, for example, Zhou et al (2022) reported that the diversity of soil bacterial communities differed between abundant and rare subcommunities and that the potential functions of rare taxa were greater than those of abundant taxa in farmlands.…”
Section: Introductionmentioning
confidence: 99%
“…Plant residues can have various positive effects on soil, such as increasing the organic matter content, improving physical properties, supplying nutrients, and enhancing beneficial microbial diversity and activity ( Tejada et al., 2009 ; Chen et al., 2016c ; Dignam et al., 2019 ). However, distinct types of plant residues may exhibit varying impacts on soil physicochemical properties and microbial communities due to their unique compositions ( Chang et al., 2022 ; Chen et al., 2022a ). TCMRs are plant residues left over after extracting active ingredients from medicinal plants.…”
Section: Introductionmentioning
confidence: 99%